The engineering potential of Rhodosporidium toruloides as a workhorse for biotechnological applications - Park,YK; Nicaud,JM; Ledesma,Amaro R (Trends in Biotechnology, 2017)
Moving our society towards a bioeconomy requires efficient and sustainable microbial production of chemicals and fuels. Rhodotorula (Rhodosporidium) toruloides is a yeast that naturally synthesizes substantial amounts of specialty chemicals and has been recently engineered to (i) enhance its natural production of lipids and carotenoids, and (ii) produce novel industrially relevant compounds. The use of R. toruloides by companies and research groups has exponentially increased in recent years as a result of recent improvements in genetic engineering techniques and the availability of multiomics information on its genome and metabolism. This review focuses on recent engineering approaches in R. toruloides for bioproduction and explores its potential as a biotechnological chassis.